Antibacterial activity of silver nanoparticles Clinacanthus nutans (Agnp-CN) against Streptococcus mutans - Siti Aisyah Abd Ghafar ,; Nor Baitie Adura Muhd Fudzi; Wan Nur Farhanah Wan Sulaiman; Vuanghao Lim; Rohazila Mohamad Hanafiah (Frontiers Media S.A, 2024)
Clinacanthus nutans was found to possess anti-venom, anti-inflammatory, analgesic, anti- diabetic, anti-rheumatism, antiviral and antioxidant properties. Silver nanoparticles are nanoparticles between 1nm to 100nm in size and play significant role in medicinal fields. Silver nanoparticles exhibit distinctive properties, such as good conductivity, chemical stability, catalytic and antibacterial activity. Streptococcus mutans is commonly found in human oral cavity and the main contributor to tooth decay. There is no study on antibacterial effect of silver nanoparticles Clinacanthus nutans (AgNp-CN) against Streptococcus mutans reported to date. Therefore, objective of this study is to investigate antibacterial properties of silver nanoparticles Clinacanthus nutans against Streptococcus mutans.